2021
DOI: 10.1101/2021.12.03.21267240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel disease mechanism leading to the expression of a disallowed gene in the pancreatic beta-cell identified by non-coding, regulatory mutations controlling HK1

Abstract: Gene expression is tightly regulated with many genes exhibiting cell-specific silencing when their protein product would disrupt normal cellular function. This silencing is largely controlled by non-coding elements and their disruption might cause human disease. We performed gene-agnostic screening of the non-coding regions to discover new molecular causes of congenital hyperinsulinism. This identified 14 non-coding de novo mutations affecting a 42bp conserved region encompassed by a regulatory element in intr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The approach to the interpretation of exome and genome sequencing data will differ between centres with some analysing variants called within a pre-defined set of known disease-causing genes whilst other laboratories will perform a gene-agnostic analysis. The latter approach has the advantage of being able to identify new genes for HI, with recent successes including the discovery of the syndromic HI genes CACNA1D , PMM2 , FOXA2 , TRMT10A , EIF2S3 , YARS , and KMT2D by exome sequencing and more recently the finding of regulatory variants deep within intron 2 of the beta-cell disallowed gene, HK1 , by genome sequencing in individuals with isolated hyperinsulinism ( 15 , 37 , 45 , 47 , 51 , 59 , 62 , 63 ). The ability of a laboratory to utilise next-generation sequencing data for genetic discovery will largely depend on their ability to perform robust genetic and functional studies to assess novel variation.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach to the interpretation of exome and genome sequencing data will differ between centres with some analysing variants called within a pre-defined set of known disease-causing genes whilst other laboratories will perform a gene-agnostic analysis. The latter approach has the advantage of being able to identify new genes for HI, with recent successes including the discovery of the syndromic HI genes CACNA1D , PMM2 , FOXA2 , TRMT10A , EIF2S3 , YARS , and KMT2D by exome sequencing and more recently the finding of regulatory variants deep within intron 2 of the beta-cell disallowed gene, HK1 , by genome sequencing in individuals with isolated hyperinsulinism ( 15 , 37 , 45 , 47 , 51 , 59 , 62 , 63 ). The ability of a laboratory to utilise next-generation sequencing data for genetic discovery will largely depend on their ability to perform robust genetic and functional studies to assess novel variation.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…Unlike targeted next-generation sequencing, which screens a predetermined list of genes, exome sequencing provides an extremely effective method to comprehensively analyse the coding regions and intron/exon boundaries of all known HI genes and to assess copy number status. The major limitation of the approach is that it will not detect non-coding mutations such as the deep intronic mutations reported in ABCC8 , HADH and HK1 or promoter variants in genes such as HNF4A , PMM2 , and SLC16A1 ( 15 , 21 , 22 , 59 , 82 ).…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…In addition, there is a good understanding of the functional impact of protein-coding variants in female infertility (Jiao et al, 2021), but less understanding of variants in non-coding regions, which accounts for 98% of the human genome. In the last decade, many studies have identified that variants in non-coding regions cause different diseases (Turro et al, 2020;Wright et al, 2021;Wakeling et al, 2022), which suggests that the analysis of non-coding regions in female infertility patients with unknown causes is also a powerful strategy to find novel pathogenic variants.…”
Section: Abnormal Activation Of the Mos-mapk Pathway In Zygotes Cause...mentioning
confidence: 99%